2019
DOI: 10.18632/aging.102262
|View full text |Cite
|
Sign up to set email alerts
|

PTEN loss regulates alveolar epithelial cell senescence in pulmonary fibrosis depending on Akt activation

Abstract: Idiopathic pulmonary fibrosis (IPF) is an aging-associated disease with poor prognosis. The mechanisms underlying the role of alveolar epithelial cell (AEC) senescence in IPF remain poorly understood. We aimed to investigate if PTEN/Akt activates AEC senescence to induce pulmonary fibrosis. We investigated the association between PTEN/Akt and cellular senescence in lung tissues from IPF patients. As a result, decreased PTEN and activated Akt pathway were found in AECs in fibrotic lung tissues detected by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 45 publications
(44 reference statements)
1
36
0
Order By: Relevance
“…Prior studies have shown that BLM treatment can effectively induce cellular senescence in alveolar epithelial cells ( Aoshiba et al, 2003 ). Cyclin-dependent kinase inhibitors p16 and p21, as well as SA-β-Gal activity are often used to confirm the appearance of senescence ( Aoshiba et al, 2013 ; Qiu et al, 2019 ). As shown in Figure 2 , both p16 and p21 gene expressions were apparently up-regulated in BLM-induced fibrotic mouse lungs, p21 protein was also significantly increased compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies have shown that BLM treatment can effectively induce cellular senescence in alveolar epithelial cells ( Aoshiba et al, 2003 ). Cyclin-dependent kinase inhibitors p16 and p21, as well as SA-β-Gal activity are often used to confirm the appearance of senescence ( Aoshiba et al, 2013 ; Qiu et al, 2019 ). As shown in Figure 2 , both p16 and p21 gene expressions were apparently up-regulated in BLM-induced fibrotic mouse lungs, p21 protein was also significantly increased compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the effects of FIS on inflammatory reaction, several common cytokines were analyzed by ELISA, which have also been suggested to be part of the SASP ( Aoshiba et al, 2013 ; Qiu et al, 2019 ). In Figure 3 , the levels of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α), profibrogenic cytokine (TGF-β) and metalloproteinase-9 (MMP-9) in the BALF of BLM-induced mice were significantly higher than those in healthy mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PTEN's role in senescence seems to be cell-type specific and can be enhancing or suppressing. While an upregulation of PTEN in alveolar epithelial cells caused senescence-associated fibrosis [36], PTEN overexpression in glioblastoma neurospheres led to increased senescence [37]. A recent study in a mouse model with conditional PTEN knockout in adipose tissue depots showed a phenotype of adipose tissue redistribution with massive expansion of the PTEN knockout depot and reduced fat mass in other adipose tissue depots.…”
Section: Discussionmentioning
confidence: 99%